Characterization of Free Surface Hydraulics Flow Over Sharp-Crested Weir in a One-Dimensional HEC-RAS Model - Mohammad Razi, Mohd Adib (International Journal of Integrated Engineering, 2020)
The current study aimed to determine the flow changes when the uses of weir hydraulic structure in an open channel hydraulic system. An experiment was conducted by using an open channel structure at the Hydrology System Station, Micro-pollutant Research Centre (MPRC), Universiti Tun Hussein Onn Malaysia (UTHM). Two (2) different types of sharp-crested weir structures which are semi-circular and triangular weir are analyzed. The experiment is conducted at same initial flow rate which is 0.270m3/s for both types of weirs. All the data required in analysis of flow characteristic such that yo, y1, y2, y3, H and Q for upstream and downstream of weirs structure was recorded. The main objective was to evaluate the flow water surface profile and energy grade line downstream of weir using Hydraulic Model (HEC-RAS). Analysis of data was conducted for physically measured and using HEC-RAS model. The results revealed that the flow at downstream had lower Fr of 0.150 compared to upstream when uses of weirs. The relationship between downstream velocity and upstream flow shows the higher the upstream flow rate, the lower the downstream velocity. HEC-RAS result shows that the upstream energy grade elevation had higher percentage difference of 24.4% from physical analysis for semi-circle weir. HEC-RAS was an effective instrument for analyzing of flow behavior in open channel and capable in evaluating the flow characteristics changes when the uses of hydraulic structure in open channel.